2020
DOI: 10.1017/s0022149x20000863
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence ofTaeniaspecies in pigs in slaughterhouses in Phu Tho province, northern Vietnam

Abstract: Pigs act as the intermediate hosts of the zoonotic tapeworms Taenia solium and Taenia asiatica, as well as of the non-zoonotic Taenia hydatigena. In Vietnam, human taeniasis and cysticercosis have been reported throughout the country; however, data on porcine cysticercosis are scarce. Our study aimed to estimate the prevalence of Taenia spp. in slaughtered pigs in two districts in Phu Tho, a mountainous province in northern Vietnam from where neurocysticercosis patients commonly originate. The carcasses of 399… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In Vietnam, 3 Taenia spp. cause human taeniasis, T. solium , T. saginata , and T. asiatica , and a recent study has also confirmed the presence of T. asiatica in pigs in Phu Tho Province [ 28 ]. This problem should be addressed in future studies by using molecular techniques.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In Vietnam, 3 Taenia spp. cause human taeniasis, T. solium , T. saginata , and T. asiatica , and a recent study has also confirmed the presence of T. asiatica in pigs in Phu Tho Province [ 28 ]. This problem should be addressed in future studies by using molecular techniques.…”
Section: Discussionmentioning
confidence: 97%
“…In conclusion, notwithstanding the improvement of hygienic standards and living conditions in Vietnam in last decades, our study has shown that T. solium transmission still occurs in communities in Phu Tho Province. The consumption of raw pork and vegetables combined with traditional pig husbandry systems, poor meat inspection procedures [ 28 , 29 ], and the common habit of using night soil on agricultural lands [ 8 ] are likely to perpetuate the transmission of tapeworm infections. Health education campaigns are needed in this area to inform the population on those infection risks.…”
Section: Discussionmentioning
confidence: 99%
“…The low prevalence of T. hydatigena (0.3%) in the sampled dogs was somewhat unexpected as in the same province Lan et al. (2011) found a prevalence of 35% in dogs, while Nguyen et al. (2020) estimated the prevalence of T. hydatigena cysticercosis in the pig intermediate host at 18%.…”
Section: Resultsmentioning
confidence: 80%
“…The finding of S. erinaceieuropaei confirms the presence of this cestode in Vietnam. This cestode has previously been found in pigs ( Nguyen et al., 2020 ) and humans ( Le et al., 2017 ) in Vietnam and is a cause of sparganosis in humans.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation